Recent progress in cassava agronomy research in Indonesia - Wargiono, J.; Kushartoyo; Suyamto, H.; Guritno, Bambang (International Center for Tropical Agriculture, 1998)
Annual growth of cassava production in the main cassava production areas during the last five years seems to have kept pace with the increase in population, while the harvested area of cassava increased only 0.6% annually. Of the total cassava produced, about 54% is used for human food, 28% for industrial purposes, 2% for feed and 16% for export. Therefore, the development of this crop should be in line with the development of other food crops and agroindustry, as well as with that of dried cassava for export. Of the total cassava area planted in the country, more than 60% is harvested during June to October. Delaying the planting of both cassava and the intercrops tends to give a similar gross return compared to that of planting in the early rainy season. Therefore, most farmers in Sumatra are now planting cassava from the early rainy season to the early dry season. Thus, the cassava harvest is more spread out and cassava becomes a more dependable crop for both the starch and pellet industries, as well as a food security crop in rural areas. Most farmers do not fertilize cassava due to lack of capital; therefore, a closer cooperation between the farmers and starch and pellet factories should be considered to solve this problem. Cassava agronomy research is mainly conducted by the Bogor and Malang Research Institutes for Food Crops, by Brawijaya University in Malang and by the Umas Jaya cassava plantation in Lampung. The yield of both cassava and intercrops grown on an ultisol in Lampung decreased more than 60% during the third consecutive cropping without any fertilizer application. Interplanted crops like maize, rice and peanut grow faster than cassava and the amounts of nutrients absorbed by these crops during the first two months are higher than for cassava under these intercropping systems. But, there is an indication that cassava absorbs residual fertilizer applied to these interplanted crops. Crop productivity could be maintained by the application of adequate amounts of fertilizer and by the incorporation of cassava stems and leaves into the soil. A balanced fertilizer rate of 75-100 kg N, 25-100 kg P2O5 and 60-100 kg K2O/ha for monoculture cassava and 100-150 kg N, 50-100 kg P2O5 and 100-150 kg K2O/ha increased net income by 70 and 370% and reduced erosion by 11 and 35%, respectively.